Environmental sustainable development of electronic manufacturing industry : a comparative study of China, India, Japan and Singapore - Liang, Peidi (2011)
As most countries’ demand for basic necessities has been satisfied since 2000, people’s focus has shifted to making resources sustainable. Another trend observed during this period is the increasingly heavy dependence on electronic products. The trend is demonstrated by the significant proportion of the countries’ GDP attributed to electronic manufacturing (EM). Being the leaders of development worldwide, China and India faces sustainability issues in EM. As the leader of Asia’s EM industry, Japan has developed unique and effective Home Appliance Regulation Laws. Singapore, the hub of R&D in EM, is adopting a totally different approach in the sustainable electronic manufacturing (SEM).